2013
DOI: 10.1016/j.juro.2012.08.092
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Concordance and Surgical Outcomes of Sporadic Synchronous Unilateral Multifocal Renal Masses Treated with Partial Nephrectomy

Abstract: In what is to our knowledge the largest published report of unilateral synchronous multifocal renal masses we document low pathological concordance rates. As such, percutaneous biopsy of a single renal mass in these patients may not help inform treatment decisions. Nephron sparing surgery may be performed with acceptable oncological and functional results in patients with unilateral synchronous multifocal renal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…In the literature, we are aware of only 2 articles that reported synchronous clear cell RCC and papillary RCC in the same kidney, similar to our case [15, 16]. Simhan et al [15] reported the data of 97 patients who had multifocal renal tumors.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the literature, we are aware of only 2 articles that reported synchronous clear cell RCC and papillary RCC in the same kidney, similar to our case [15, 16]. Simhan et al [15] reported the data of 97 patients who had multifocal renal tumors.…”
Section: Discussionsupporting
confidence: 77%
“…Simhan et al [15] reported the data of 97 patients who had multifocal renal tumors. They reported 8 patients who had mixed (papillary and clear cell) RCC, all of which were treated by PN.…”
Section: Discussionmentioning
confidence: 99%
“…1 Traditionally, patients with unilateral synchronous multifocal disease were treated with radical nephrectomy (RN), thus avoiding possible residual ipsilateral lesions and achieving maximal oncologic benefit, despite the negative effects on renal function and risk of subsequent chronic kidney disease (CKD). 2,3 Recent reports indicate that partial nephrectomy (PN) for multifocal renal cortical tumors offers equivalent cancer-specific survival (CSS) to RN, with the added benefit of preservation of postoperative renal function with a limited complication profile. 35 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Recent reports indicate that partial nephrectomy (PN) for multifocal renal cortical tumors offers equivalent cancer-specific survival (CSS) to RN, with the added benefit of preservation of postoperative renal function with a limited complication profile. 35 …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Simhan et al 19 reported a data of 97 patients who had multifocal renal tumors. They reported 8 patients who had mixed papillary and clear cell RCC, all of which were treated with partial nephrectomy.…”
Section: Discussionmentioning
confidence: 99%